Clinical Subtypes and Prognostic Outcomes of Rhabdomyolysis in ICU Patients - Shan Xu; Kaixiu Qin; Dan Zhang (International Journal of Clinical Practice)
Conclusions: We identified two subtypes with distinct clinical features and outcomes. Subtype A is independently associated with poor outcomes and shows increased mortality risk with sodium bicarbonate use. These findings may help clinicians better distinguish prognoses and treatment responses among RM patients.